Planning in Germany and Iran. Responding to challenges of climate change through intercultural dialogue. - (:unkn) unknown (mbv, Mensch u. Buch, 2021)
These peer-reviewed papers reflect the intensive inter- and transdisciplinary collaboration between the project members of the TU Dortmund University and DHEI and its Iranian partner universities such as Tarbiat Modares University (TMU)/Tehran, Sheikh Bahaei University/Esfahan, and Yazd University/Yazd. The papers were produced over two years of joint workshops, research visits, spring and winter schools, and a training program at TUDO:. Sections: (1) Environmental Approaches to Climate Change Challenge; (2) Urban Approaches to Climate Change Challenge; (3) Social Approaches to Climate Change Challenge; (4) Architectural Approaches to Climate Change Challenge.
Keywords: Klimawandel; Klimafolgenanpassung; Resilienz; Umweltplanung; Kommunaler Klimaschutz; Traditionelles Bauen; Architektur; Städtebau; Internationale Zusammenarbeit; Projektbeispiel